A HYPOTHETICAL MODEL FOR THE RELATIONSHIP BETWEEN TEACHERS’ JOB SATISFACTION, BURNOUT AND PERCEPTIONS OF INDIVIDUALPERFORMANCE - Zincirli, Muhammed (My University, 2021)
This study aims at determining the relationships between teachers' job satisfaction, burnout and individual performance perceptions. The study was designed in relational screening model. The participants of the study comprised 359 volunteer teachers who were selected using appropriate sampling method in state schools in Elazığ province of Turkey. The data were collected via the Job Satisfaction Scale, the Burnout Scale, and the Individual Performance Scale in 2019-2020 academic year. In the data analysis process, descriptive statistics and Pearson moment product correlation coefficient were used to reveal the relationships between the variables. In addition, Structural Equation Model was used to determine the direct predictors of teachers’ perception of job satisfaction and burnout on individual performance perception. The bootstrapping through the structural equation model was used in order to determine the indirect predictive power of teachers’ perception of job satisfaction on their perception of individual performance through their perception of burnout. The results showed that there were negative and positive significant relationships between teachers’ job satisfaction, burnout and individual performance perceptions. It was found that teachers’ job satisfaction perception significantly predicted burnout perception negatively (? = -.40; p <0.01) whereas it positively and significantly predicted individual performance perception (? = .37; p <0.01). In addition, Teachers’ burnout perception predicted their individual performance perceptions negatively and significantly (= -.28; p <0.01). Furthermore, it was revealed that teachers’ job satisfaction perceptions had an indirect predictive (mediating) effect on individual performance perception through burnout perception. As a result, it was determined that the theoretical model and hypotheses as to the relationship between teachers’ job satisfaction, burnout and individual performance perceptions were statistically verified.
Keywords: Eğitim; Eğitim Araştırmaları; Psikoloji